Blue diode-pumped single-longitudinal-mode Pr:YLF lasers in orange spectral region. (October 2020) - Zhang, Yunshan; Zhou, Lunbin; Zhang, Teng; Cai, Yaqi; Xu, Bin; Xu, Xiaodong; Xu, Jun
Highlights: A Pr:YLF-based single-frequency orange laser at 607 nm has been first demonstrated. A Pr:YLF-based single-frequency orange laser at 604 nm has been first demonstrated. The single-frequency orange lasers have potential application in biomedicine. Abstract: We report on blue diode-pumped single-frequency Pr:YLF lasers in orange spectral region, for the first time to the best of our knowledge. For a single-frequency σ-polarized 607 nm laser, a maximum output power up to 175 mW is achieved with a slope efficiency of about 16.6%. Linewidth of the 607 nm single-frequency laser is measured to be about 6 MHz. Single-frequency operation has also been obtained at π-polarized 604 nm laser with a maximum output power up to 91 mW and a slope efficiency of about 8.9%. The corresponding linewidth of the 604 nm laser is about 22 MHz. The two single-frequency orange lasers exhibit wavelength tuning ranges of about 0.15 nm and 0.35 nm, respectively. This work has proposed the simplest way for single-frequency laser generation in orange spectral region, which could be obtained by complicated and low-efficiency sum-frequency mixing of Nd 3+ lasers. This work paves a practical way for various orange-related applications.